The interplay between histone deacetylases and c-Myc in the transcriptional suppression of HPP1 in colon cancer - Wang, Jian (Landes Bioscience, 2014)
HPP1 (hyperplastic polyposis protein 1), a tumor suppressor gene, is downregulated by promoter hypermethylation in a number of tumor types including colon cancer. c-Myc is also known to play a role in the suppression of HPP1 expression via binding to a promoter region cognate E-box site. The contribution of histone deacetylation as an additional epigenetic mechanism and its potential interplay with c-Myc in the transcriptional regulation of HPP1 are unknown. We have shown that the treatment of the HPP1-non-expressing colon cancer cell lines, HCT116 and DLD-1 with HDAC inhibitors results in re-expression of HPP1. RNAi-mediated knockdown of c-Myc as well as of HDAC2 and HDAC3 in HCT116 and of HDAC1 and HDAC3 in DLD-1 also resulted in significant re-expression of HPP1. Co-immunoprecipitation (IP), chromatin IP (ChIP), and sequential ChIP experiments demonstrated binding of c-Myc to the HPP1 promoter with recruitment of and direct interaction with HDAC3. In summary, we have demonstrated that c-Myc contributes to the epigenetic regulation of HPP1 via the dominant recruitment of HDAC3. Our findings may lead to a greater biologic understanding for the application of targeted use of HDAC inhibitors for anti-cancer therapy.